Supplementation of L-glutamine enhanced mucosal immunity and improved hormonal status of combat-sport athletes - Tung-Lin Lu; Ai-Chi Zheng; Katsuhiko Suzuki; Chi-Cheng Lu; Chung-Yuan Wang; Shih-Hua Fang (Journal of the International Society of Sports Nutrition)
Background Maintaining proper immune function and hormone status is important for athletes to avoid upper respiratory tract infection (URTI) and insufficient recovery, which is detrimental to sport performance and health. The aim of this study was to evaluate whether three-week supplementation of L-glutamine could benefit the mucosal immunity and hormonal status of combat-sport athletes as well as their rates of upper respiratory tract infection (URTI) and subjective feelings of well-being after intensive training.Methods Twenty-one combat-sport athletes from the National Taiwan University of Sport were recruited in this study. After intensive training, two groups of the participants were asked to consume powder form of 0.3 g/kg body weight of L-glutamine (GLU group) or maltodextrin (PLA group) with drinking water in a randomized design at the same time every day during 3 weeks. Saliva samples were collected to measure immunoglobulin A (IgA), nitric oxide (NO), testosterone (T) and cortisol (C) before and after three-week supplementation; moreover, Hooper’s index questionnaires were completed for wellness assessment. The incidence and duration of URTI were recorded by using a health checklist throughout the entire study period.Results Supplementation of L-glutamine significantly enhanced the concentrations of IgA and NO in saliva; additionally, the incidence of URTI was significantly reduced. Regarding hormones, T concentration was significantly decreased in the PLA group, whereas C concentration was significantly increased, resulting in a significant decrease of T/C ratio. In contrast, the GLU group showed a significant increase of T/C ratio, while the mood scores of the Hooper’s index questionnaire were higher in the PLA group.Conclusions Three-week supplementation of L-glutamine after intensive training enhanced the mucosal immunity, improved hormonal status and reduced the rate of URTI of combat-sport athletes while feelings of well-being were also enhanced. Therefore, L-glutamine would be beneficial for the sports performance and recovery of athletes.